If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying Y = (15x + 10)(15x + -2) Reorder the terms: Y = (10 + 15x)(15x + -2) Reorder the terms: Y = (10 + 15x)(-2 + 15x) Multiply (10 + 15x) * (-2 + 15x) Y = (10(-2 + 15x) + 15x * (-2 + 15x)) Y = ((-2 * 10 + 15x * 10) + 15x * (-2 + 15x)) Y = ((-20 + 150x) + 15x * (-2 + 15x)) Y = (-20 + 150x + (-2 * 15x + 15x * 15x)) Y = (-20 + 150x + (-30x + 225x2)) Combine like terms: 150x + -30x = 120x Y = (-20 + 120x + 225x2) Solving Y = -20 + 120x + 225x2 Solving for variable 'Y'. Move all terms containing Y to the left, all other terms to the right. Simplifying Y = -20 + 120x + 225x2
| 3(2a-b)-5a= | | 7v+2=0 | | 2x-4x+4=x-3+7 | | 7=3(t-5)-t | | 3x^2-2x-8=448 | | Y=225x^2+120x+20 | | 1.3x+1.6y=.6 | | 15x-150=90 | | -8-2(8n-8)=-6n+8 | | 5x-2x-3=27 | | -76+n=-115 | | 6tx=4+2 | | 5x-6+6/5=14+6/5 | | 3a+8+a-9-2= | | 15=9w | | 10x+34=114 | | (x+2)2=13 | | -13+3x=-52+24 | | 4cos^2(x)+1=3 | | 5x+6+6/5=16+6/5 | | 8p+2=4-10 | | 5x+59=99 | | 3+2*(-x+4)= | | 6x=-4x^2 | | 16x+68=180 | | -6+8k=4(1+4k)-6k | | 7-15t=5s-3 | | 4x+-15=17+-4x | | w*W+16=8w | | 25=7+3k-n | | 11x+136=180 | | 7x-10=4x+10 |